OPERATIONAL COSTS OF GIANT BAMBOO CULTIVATION IN DIFFERENT SOIL PREPARATION SYSTEMS - correia, Tiago Pereira da Silva; Fontana, João Lucas Cotrim; Lopes, Arthur Gabriel Caldas; Pereira, Reginaldo Sérgio; Silva, Paulo Roberto Arbex (ENERGIA NA AGRICULTURA, 2020)
OPERATIONAL COSTS OF GIANT BAMBOO CULTIVATION IN DIFFERENT SOIL PREPARATION SYSTEMS TIAGO PEREIRA DA SILVA CORREIA1, JOÃO LUCAS COTRIM FONTANA2, ARTHUR GABRIEL CALDAS LOPES2, REGINALDO SÉRGIO PEREIRA1, PAULO ROBERTO ARBEX SILVA3 1 Faculdade de Agronomia e Med. Veterinária, Universidade de Brasília, Brasília, Distrito Federal, CEP70910-900, Brasil, tiagocorreia@unb.br, reginaldosp@unb.br 2 Faculdade de Agronomia e Med. Veterinária, Universidade de Brasília, Brasília, Distrito Federal, Brasil, arthur.grb10@gmail.com, fontanajlc@gmail.com 3 Faculdade de Ciências Agronômicas, Universidade Estadual Paulista “Julio de Mesquita Filho”, Botucatu, São Paulo, CEP18610-034, Brasil, paulo.arbex@unesp.br ABSTRACT: One of the bottlenecks for expanding commercial bamboo farming in Brazil is agricultural mechanization. The aim of this work was to evaluate the operational performance and to estimate the mechanized cost of soil preparation and planting of giant bamboo in four cultivation systems. The case study of mechanized systems for giant bamboo cultivation was carried out in: area of degraded pasture with conventional soil preparation (PC1); area of eucalyptus regrowth with conventional soil preparation (PC2); area of degraded pasture and no-tillage (PD1) and area of eucalyptus regrowth and no-tillage (PD2). Evaluations of operational field capacity (Cco) were performed to determine the amount of work performed per machine per hour, and total cost (COT) to economically estimate hourly and per hectare costs of operations. The methodology used was proposed by Mialhe (1974) and ASABE (2006). Except for PC2, the planting operation represents a larger share of total costs; direct planting in PD1 and PD2 allows fewer activities in the soil tillage operation and consequent cost reduction. PD1 is recommended. Keywords: Dendrocalamus asper, soil preparation, planting, mechanization; agricultural operations. CUSTOS OPERACIONAIS DO CULTIVO DE BAMBU GIGANTE EM DIFERENTES SISTEMAS DE PREPARO DO SOLO RESUMO: Um dos gargalos para expandir o cultivo comercial de bambu no Brasil é a mecanização agrícola. O objetivo deste trabalho foi avaliar o desempenho operacional e estimar o custo mecanizado do preparo do solo e plantio de bambu gigante em quatro sistemas de cultivo. Foi realizado o estudo de caso de sistemas mecanizados de cultivo de bambu gigante em: Área de pastagem degrada com preparo convencional do solo (PC1); área de rebrota de eucalipto com preparo convencional do solo (PC2); área de pastagem degradada e plantio direto (PD1) e área de rebrota de eucalipto e plantio direto (PD2). Foram avaliadas: capacidade de campo operacional (Cco) para determinar a quantidade de trabalho realizado por máquina por hora; custo operacional (CO) e custo total (COT) para estimar economicamente os gastos por hora e por hectare nas operações. A metodologia utilizada foi a proposta por Mialhe (1974) and ASABE (2006). Exceto o PC2, a operação de plantio representa maior participação nos custos totais; o plantio direto em PD1 e PD2 possibilita menor número de atividades na operação de preparo do solo e consequente redução dos custos. Recomenda-se o PD1. Palavras-chave: Dendrocalamus asper, preparo do solo, plantio, mecanização, operações agrícolas.